Discount pricing - Armstrong, M; Chen, Y (Wiley, 2019)
We investigate the practice of framing a price as a discount from an earlier price, with information such as "was USD200, now USD100". We discuss two reasons why a discounted price- rather than a merely low price- can make a consumer more willing to purchase. First, a high initial price can indicate the seller has chosen to supply a high-quality product. Second, when a seller with limited stock runs a clearance sale, later consumers infer that unsold stock has higher expected quality when its initial price was higher. We also suggest a behavioural explanation, which is that consumers with reference-dependence preferences are more likely to buy if they perceive the price as a bargain relative to the earlier price. Discount pricing is therefore an effective marketing technique, and a seller may wish to deceive potential customers by offering a false discount. The welfare effects of regulation to prevent fictitious pricing are subtle, possible with unintended consequences, partly depending on whether consumers are sophisticated or naive.